Exploring the suitability of WhatsApp as a Communication Tool for Mthisman Investment & Other Logistics Truck drivers - Matsane, Mando (The IIE, 2020)
In this study the researcher sets out to explore the perceptions of Mthisman Investment & Other Logistics truck drivers in Gauteng towards the suitability of WhatsApp as a work related communication Tool. A qualitative study was conducted using semi-structured interviews to gain an in-depth understanding of respondents’ views on WhatsApp as a work-related communication tool. A data analysis was done on the transcribed interview responses and results show that the truck drivers do consider WhatsApp as a suitable communication tool with communication suitability as the most mentioned theme. All the truck drivers felt that WhatsApp as a communication tool is an advantage and had few disadvantages to mention. Overall communication suitability seemed to be the most important for Mthisman Investment & Other Logistics Truck Drivers within the Gauteng Region.
Keywords: WhatsApp; Communication suitability; Transport industry; Communication effectiveness